Hip hop Practice as Identity and Memory Work in and In-between Chile and Sweden - Susan Lindholm (Suomen Antropologi, 2017)
Over 40 years have passed since the coup d’état in Chile on September 11th 1973. Although Augusto Pinochet’s military regime officially came to an end in 1990, the political and societal consequences of the coup and 17 years of dictatorship live on to this day, both in and outside of Chile. In this article I discuss hip hop practice as a form of identity and memory work in, and in-between Chile and Sweden, the country that welcomed the highest number of Chilean refugees in Europe after the coup. I focus on those instances in which rappers in both Sweden and Chile refer to specific versions of the past in their lyrics, music, videos, biographies, and in TV programs. My analysis shows that artists in both countries use hip hop culture in order to create meaning and a sense of shared history by engaging in strategic and self-conscious identity and memory work.